An All-Solid-State Lithium Metal Battery Based on Electrodes-Compatible Plastic Crystal Electrolyte - Bin Zhao (MDPI AG, 2021)
Solid-state plastic crystal electrolytes (SPCEs) have attracted much attention due to their high ionic conductivity at room temperature and polymer-like plasticity. Herein, we made a LiFePO4||Li solid state battery based on SPCEs. A SPCE film is made up of glass fiber, succinonitrile (SN), lithium bis (triflu-romethanesulphonyl) imid (LiTFSI), and LiNO3. Glass fiber is introduced to improve the mechanical property, and LiNO3 served as an additive to stabilize electrolyte/Li interface. The SPCE film delivers a high ionic conductivity of 7.3 × 10−4 S cm−1 at room temperature and has excellent stability with Li-metal anode. SPCE is also infused into cathode electrode and used as the interface with cathode particles, which can access a large interface contact area and deform reversibly with volume change. The LiFePO4||Li solid state battery based on SPCE can work well at ambient temperature, which shows a high initial specific capacity of 121.4 mAh g−1 and has 86.9% retention after 90 cycles at 0.5 C.